(untitled) (Eurasian Research Bulletin, 2025)
The article is devoted to the analysis of noise sources, their norms, and acoustic characteristics arising in machine-building, machine-building, and blacksmithing workshops using the example of JSC "Tashkent Passenger Car Construction and Repair Plant." The study recorded more than 100 types of technological equipment available in large industrial workshops, and their contribution to the acoustic load was studied in detail. In the mechanical engineering workshop, the main sources of noise were hydraulic presses and screw compressors, and the sound pressure was measured in the range of 74-103 dB. In the machine shop, it was found that the sheet folding and plasma units emit noise in the range of 80-106 dB. The highest noise levels were observed in the blacksmith shop, where the sound pressure during the manufacture of wagon springs reached 118- 122 dB. Also, the noise generated by chisel hammers and mechanical presses was recorded in the range of 115-130 dB, and in metal-cutting machines - in the range of 105- 115 dB. Mechanical, aerodynamic, hydrodynamic, and electromagnetic types of noise are classified according to their origin, and their frequency ranges and spectral characteristics are indicated. Normative standards were analyzed in accordance with the requirements of SanPiN RUz N 0325-16 and GOST 12.1.050-86. The levels of sound pressure at workplaces were assessed in octave frequency bands, and the compliance of working conditions with sanitary and hygienic requirements was determined. The research results show that to reduce noise, technological and structural optimization of the source, the use of acoustic barriers in the path of propagation, and personal protective equipment are necessary. As recommendations, it is proposed to install acoustic screens in the operator’s seats, use high-frequency absorbing materials, and develop innovative technical solutions. This approach is relevant in protecting workers’ health, preventing occupational diseases, and increasing labor productivity.